Performance and microbial communities of a novel integrated industrial-scale pulp and paper wastewater treatment plant. (1st January 2021) - Liang, Jiawei; Mai, Wenning; Wang, Jia; Li, Xiaoqi; Su, Minhua; Du, Jiaxu; Wu, Yanwei; Dai, Jihua; Tang, Qi; Gao, Jihong; Liu, Yingkui; Tang, Jinfeng; et al.
Abstract: Paper production generates pulp and paper wastewater (PPW), and it is difficult to remove the high-level pollutants in PPW efficiently. Herein, an efficient industrial-scale pulp and paper wastewater treatment plant (PP-WWTP) that integrated physicochemical and biological processes is investigated and reported. This PP-WWTP treated 2.3 Mt of wastewater with 17, 388 ± 1436 mg/L chemical oxygen demand (COD) annually. The PP-WWTP can effectively remove over 99.81% of the COD. In detail, the physical, anaerobic, aerobic and chemical steps accounted for 41.6%, 40.0%, 11.9%, and 6.5% of COD removal, respectively. The microbial communities of the bioreactors removed the pollutants efficiently and contained diverse microbes. Further metagenomic analyses of the bioreactors identified more than 90, 000 genes/gene fragments encoding for carbohydrate-active enzymes (CAZys), demonstrating high lignocellulose degradation ability of the bioreactors at molecular level. The xylanase activity assay showed some lignocellulase in the bioreactors were functional. Recycling the residual heat from the PPW along with energy recovered from biological treatment of the PPW, in the form of biogas (20, 000 m³/d), could generate more than 1.5 M USD benefits/y. The results of this study demonstrated that the integrated physicochemical and biological process for PPWW treatment could effectively remove pollutants while generating revenue. Graphical abstract: Image 1 Highlights: An integrated process was applied in an industrial-scale pulp and paper wastewater treatment plant. Most pollutants were removed in the biological part of the integrated process. The wastewater treatment can generate benefits. The high efficient COD removal ability was driven by large amounts of lignocellulase genes.